Pendidikan Life Skill dalam Keluarga Penambang di Kawasan Pertambangan Batu Bara di Merancang Ulu - Dwi Rizki Yuliani (Rayhan Intermedia, 2019)
This study aims to find out: (1) knowing how life skill education takes place in the family of Merancang Ulu, Gunung Tabur, Berau, East Kalimantan coal miners, (2) knowing how the factors that influence the occurrence of life skill education in Merancang Ulu Coal Mountain family, Gunung Tabur, Berau, East Kalimantan, (3) find out how the impacts generated from life skills education in the family of Merancang Ulu, Gunung Tabur, Berau, East Kalimantan coal miners. In this study used a type of qualitative research that was analyzed and written descriptively. Data collection techniques were carried out using the method of observation, interviews, and documentation involving 10 (ten) informants. The theory used is Piaget's constructivism theory. Based on the results of the study, it shows that: (1) the process of life skill education takes place in the family of coal miners (A case study of the community around the Merancang Ulu mining area is starting from the habit of paying attention, seeing the work routines of parents who work in mining every day) coal, then arises a sense of curiosity about how the work, there is an end in asking there are also those who seek information themselves, after the child knows then tells a parent (father and mother) discuss and then ask for opinions about the work. (2) factor -factors that occur in the family of coal miners, both external and internal factors, both of which certainly encourage the occurrence of the case, the same as the life skill of the child who follows in the footsteps of his parents (father) to work in coal mining. (3) As for the impact caused by the results of life skill education in the penamba family When talking about the impact, there are certainly two impacts that are produced, namely positive and negative impacts.